2022
DOI: 10.3389/fpsyg.2022.875848
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Dynamic Dual Pathway Model of Approach Coping to Collective Action Among Advantaged Group Allies and Disadvantaged Group Members

Abstract: We apply the dynamic dual pathway model of approach coping to understanding the predictors of future collective action among a sample of advantaged group allies and disadvantaged group members who were attending a protest. We propose that problem-focused approach coping (i.e., group efficacy beliefs) would be a stronger predictor of future collective action among disadvantaged compared to advantaged group members, and emotion-focused approach coping (i.e., group-based anger) would be a stronger predictor of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Conversely, when anger or rage is not directed towards a clear and specific goal, it tends to manifest as anxiety, not in a way beneficial to the movement and the individuals participating in it ( Van Ness and Summers-Effler, 2018 ). Also, increased group anger has been found to be a predictor of future collective action intentions ( Tausch and Becker, 2013 ; Radke et al, 2022 ). On the other hand, it has been found that anger can be more relevant to collective action when activists are members of a disadvantaged group ( Landmann and Rohmann, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, when anger or rage is not directed towards a clear and specific goal, it tends to manifest as anxiety, not in a way beneficial to the movement and the individuals participating in it ( Van Ness and Summers-Effler, 2018 ). Also, increased group anger has been found to be a predictor of future collective action intentions ( Tausch and Becker, 2013 ; Radke et al, 2022 ). On the other hand, it has been found that anger can be more relevant to collective action when activists are members of a disadvantaged group ( Landmann and Rohmann, 2020 ).…”
Section: Introductionmentioning
confidence: 99%